The Relationship between Poor Executive Functioning and Social Functioning and the Efficacy of Brain Training on Social Functioning - Zahra Husseini; Vahid Nejati; Mojtaba Habibi (Shiraz University of Medical Sciences, 2019)
Background: Brain processes are controlled and directed by some brain functions called Executive Functioning. Poor EF affects amelioration of brain functions and related behaviors in social and academic life. In the present research, we investigated the relationship between EF and social functions and tested the brain training effect on EF and social functioning improvement. Methods: The present study aims to investigate the correlation between poor EF and social self-efficacy and social adjustment and examine the efficacy of cognitive EF training on selected components of social functioning. Through available sampling, 369 healthy high school students aged 16-18 participated in the experiment who were randomly assigned into experimental and control groups; the experimental group consisted of 183 persons (105 girls and 78 boys) and the control group consisted of 186 persons (117 girls and 69 boys). Main EF processes (working memory, shifting, inhibition and problem solving) and social functions (social adjustment and social self-efficacy) were assessed and their correlations were measured. In a randomized controlled trial with pretest, post-test and follow-up assessment, the effects of cognitive brain training was studied on self-efficacy and social adjustment performance of the experimental group. The intervention tool was Practical Cognitive Strategy Training (PCST) which used cognitive awareness, cognitive strategy training and cognitive training to accomplish both goals of EF training in twelve ninety-minute sessions, once a week. Results: Result showed significant moderate correlation between social and executive functions (p ≤ .001). After twelve weeks of brain training practice, participants showed a significant difference in social adjustment and self-efficacy compared with the control group. The pre-, post- and follow-up tests were timeconsuming and might have affected the results. Conclusion: Social functions correlate with EF performance and cognitive brain training can improve social adjustment and self-efficacy.